2019
DOI: 10.1109/access.2019.2942957
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Fabrication of Cold Drawn Steel Wire Through Classification and Clustering Machine Learning Algorithms

Abstract: The demanding deformations steel is subjected to during drawing may result in the breakage of the wire. The hypothesis of this research is that drawing failure is not a random event but can be predicted using a suitable approach. Machine Learning classification and clustering algorithms have been implemented to predict the probability of failure during drawing and to optimize the manufacturing conditions to reduce the failure rate. The following algorithms have been employed for classification: K-Nearest Neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In terms of the simulation studies, there are numerous articles based on either commercial software such as Ansys, Abaqus, et cetera or in-house coding software such as Matlab, Arduino, Python et cetera that can be followed by the concept of machine learning and deep learning approaches to predict the possibility of any failure during or after cold working to optimize the manufacturing processes to decrease the failure rate. For instance, as for the implementation of classification and clustering algorithms, Ruiz et al [54] used the K-Nearest Neighbors (KNN), Random Forests, and Artificial Neural Networks algorithms for classification. The study showed that the heats, considering a greater possibility of undergoing any failure during wire drawing of steel, were detected and, consequently, caused to enhance the product final quality.…”
Section: Mechanical Behavior During and After Cold Plastic Deformationmentioning
confidence: 99%
“…In terms of the simulation studies, there are numerous articles based on either commercial software such as Ansys, Abaqus, et cetera or in-house coding software such as Matlab, Arduino, Python et cetera that can be followed by the concept of machine learning and deep learning approaches to predict the possibility of any failure during or after cold working to optimize the manufacturing processes to decrease the failure rate. For instance, as for the implementation of classification and clustering algorithms, Ruiz et al [54] used the K-Nearest Neighbors (KNN), Random Forests, and Artificial Neural Networks algorithms for classification. The study showed that the heats, considering a greater possibility of undergoing any failure during wire drawing of steel, were detected and, consequently, caused to enhance the product final quality.…”
Section: Mechanical Behavior During and After Cold Plastic Deformationmentioning
confidence: 99%
“…The fabrication of cold forming steel comprises the following four major stages: electric arc furnace (EAF), ladle furnace (LF), continuous casting (CC) and hot rolling (HR). These are briefly described hereafter [23][24][25]:…”
Section: Cold Heading Steel: Properties and Fabricationmentioning
confidence: 99%